Isotopic composition of air trapped in EPICA Dome C and Talos Dome ice cores in order to constrain the influence of orbital forcing and greenhouse gases on glacial–interglacial variations - Bazin, Lucie (HAL CCSD, 2015)
In order to study the climate variations recorded by ice cores, it is necessary to have precise chronologies for the ice and gas phases. The aim of this work has been to improve ice cores chronologies, covering the last 800 000 years, through new measurements of the isotopic composition of the air δ15N, δ18Oatm et δO2/N2) trapped in EPICA Dome C (EDC) ice core and the use of the Datice dating tool.The first important result of this PhD has been the production of the Antarctic Ice Core Chronology (AICC2012), common for EDC, Vostok, EPICA Droning Maud Land (EDML), TALos Dome ICE core (TALDICE) and NorthGRIP ice cores. The bipolar see-saw theory is still valid on the new chronology. The AICC2012 chronology gives an age for Termination II in good agreement with other climate archives. Moreover, the duration of interglacial periods is unchanged compared to EDC3. While building the AICC2012 chronology, we have pointed out several limitations. Since then, we have improved Datice in order to correctly integrate constraints deduced from layer counting and their associated uncertainties. These improvements permit to build coherent chronologies respecting the underlying hypotheses of Datice. Moreover, we propose a new parameterization of the uncertainty associated with the background thinning function based on ice mechanical properties of EDC ice core. Finally, we were able to deduce new age constraints thanks to the new measurements of δO2/N2 and δ18Oatm performed on well-conserved ice from EDC. A multi-proxy comparison of Vostok, EDC and Dome F ice cores over MIS 5 has highlighted a possible influence of local climatic parameters on δO2/N2. The analysis of the delay between δ18Oatm and precession shows some variability over the last 800 ka. We propose that the delay between δ18Oatm and precession is increased during periods associated with Heinrich events. The results obtained during this PhD should be used for the next ice core coherent chronology. Afin d’étudier les variations climatiques enregistrées par les ...